NEW VARIETY OF RHODONITE FROM MANGANESE SHOWS OF THE POLAR URALS - Taran M.N.; Silayev V.I.; Khomenko V.N.; Ivanova I.B.; Zharikov V.A. (My University, 1989)
A lilac- to violet-colored mineral subsequently identified as rhodonite was found by I.B. Ivanova in a carbonate-manganese ores of the Polar Urals in 1985. The manganese show consisted of a lens within Riphaean chlorite-amphibolite schist alternating with carbonate partings. The rhodonite was found in the carbonate pockets and in small lenses in the gondite, in association with minerals of the maganocalcite-rhodochrosite series and with the sporadic occurrence of manganese silicate (friedelite). To determine the cause of the above coloration and pleochroism, which are unusual in silicates of divalent manganese, we investigated the polarized-light absorption spectrum of the violet variety of rhodonite. We conclude that the unusual coloration and pleochroism of this rhodonite result from the presence of impurity CoVI2+ in it. So far as we are aware, this is the only known case of divalent cobalt ions in octahedral structural positions of natural silicates. The presence of Co2+ ions in octahedral structural positions and the fact that this mineral almost completely lacks the impurity iron that is usual in pink rhodonite suggest that our specimen is a new variety, an iron-free, cobalt-containing rhodonite (cobalt-rhodonite) with a characteristic violet color. Thus, the existence of organic isomorphism in the series (Ca,Mn)(Fe, Mn)Mn3Si5O15 (rhodonite) and (Ca, Mn)(Co, Mn)Mn3Si5O15 (cobalt-rhodonite) under particular geochemical conditions is now demonstrated.